Locked in: the true causes of mass incarceration - and how to achieve real reform - Pfaff, John F. (Basic Books, 2017)
"Pfaff argues that existing accounts of the causes of mass incarceration are fundamentally misguided. The most widely accepted explanations--the failed War on Drugs, draconian sentencing laws, an increasing reliance on private prisons--actually tell us much less than we like to think. Instead, Pfaff urges us to look at other factors, including a major shift in prosecutor behavior that occurred in the mid-1990s, when prosecutors began bringing felony charges against arrestees about twice as often as they had before"--Amazon.com